Critical points for an accurate human genome analysis. Issue 8 (16th June 2017) - White, Stefan J.; Laros, Jeroen F.J.; Bakker, Egbert; Cambon‐Thomsen, Anne; Eden, Martin; Leonard, Samantha; Lochmüller, Hanns; Matthijs, Gert; Mattocks, Christopher; Patton, Simon; Payne, Katherine; Scheffer, Hans; et al.
Abstract: Next‐generation sequencing is radically changing how DNA diagnostic laboratories operate. What started as a single‐gene profession is now developing into gene panel sequencing and whole‐exome and whole‐genome sequencing (WES/WGS) analyses. With further advances in sequencing technology and concomitant price reductions, WGS will soon become the standard and be routinely offered. Here, we focus on the critical steps involved in performing WGS, with a particular emphasis on points where WGS differs from WES, the important variables that should be taken into account, and the quality control measures that can be taken to monitor the process. The points discussed here, combined with recent publications on guidelines for reporting variants, will facilitate the routine implementation of WGS into a diagnostic setting.